2023
DOI: 10.1101/2023.02.12.23285701
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterizing the use of the ICD-10 Code for Long COVID in 3 US Healthcare Systems

Abstract: The International Classification of Diseases (ICD)-10 code (U09.9) for post-acute sequelae of COVID-19 (PASC) was introduced in October of 2021. As researchers seek to leverage this billing code for research purposes in large scale real-world studies of PASC, it is of utmost importance to understand the functional use of the code by healthcare providers and the clinical characteristics of patients who have been assigned this code. To this end, we operationalized clinical case definitions of PASC using World He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 13 publications
0
15
0
Order By: Relevance
“…8). We found that an average of 42.3% patients assigned the U09.9 code were hospitalized after infection, and an average of 12.3% received intensive care -both of which can produce long-lasting symptoms that overlap with long COVID 5 . Physical and physiological effects of hospitalization or critical care are important patient-level factors that should not be misattributed to SARS-CoV-2 infection.…”
mentioning
confidence: 93%
See 4 more Smart Citations
“…8). We found that an average of 42.3% patients assigned the U09.9 code were hospitalized after infection, and an average of 12.3% received intensive care -both of which can produce long-lasting symptoms that overlap with long COVID 5 . Physical and physiological effects of hospitalization or critical care are important patient-level factors that should not be misattributed to SARS-CoV-2 infection.…”
mentioning
confidence: 93%
“…We are an international consortium that has operationalized definitions of long COVID using health-agency guidelines, and established a chart-review procedure based on these definitions 5 . During this process, we identified three major challenges in using real-world data to study long COVID: ambiguity and heterogeneity in clinical coding of long COVID; inadequacy of diagnostic codes in capturing the constellation of symptoms; and biases in EHR data arising from variability in the number and kind of contacts with the healthcare system.…”
mentioning
confidence: 99%
See 3 more Smart Citations